A class of meromorphic Bazilevič-type functions defined by a differential operator - Arif, M.; Ahmad, Q. Z.; Noor, K. I.; Orhan, H.; Khan, N. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.54 We define a new subclass of meromorphic Bazileviˇc-type functions by using a differential operator. We study someinteresting properties, such as the arc length, the growth of coefficients, and the integral representation of functions fromthis class.